An Analysis of Reasons Why Widows Join Stokvels: An Eastern Cape Story - Samson Adeoluwa Adewumi; Anthony Kambi Masha; Patrick Bwowe (E-Journal of Humanities, Arts and Social Sciences)
Stokvels are frequent unofficial gatherings of individuals who choose to unite for improvement their living circumstances. They contribute to the development of social capital in society, particularly for women. Hence, the motivations behind widows joining stokvels were investigated in this study. To collect data, members of stokvels were given a questionnaire with 13 questions. On a scale of 1 to 5, with 5 denoting strongly agree, 4 agree, 3 somewhat agree, 2 disagree, and 1 strongly disagree, respondents were required to react by placing an “X” on the corresponding number. Due to their low loadings and substantial variations, questions 4, 7, and 9 have been eliminated. The reliability or internal consistency of the study’s questionnaire was assessed using the Cronbach Alpha Coefficient. A score of 0.8 was considered an acceptable level of internal reliability. Structural Equation Modelling (SEM) was used to test the data after it had been analysed using statistical methods. The relationship between the variables in this study was defined through this process. Widows join stokvels for a variety of reasons, including social and financial ones, according to the study. Hence, widows should understand why they join stokvels according to the study’s findings. To obtain detailed descriptions of participants’ opinions in their natural environments, the study suggested that future research of this kind should employ a qualitative research methodology.